Assessing microcirculation condition in critical illness using the pulse oximeter's concept - Mohamad Suhaimi F.; Chase J.G.; Le Compte A.J.; Pretty C.G.; Elliott R.; Wenz A.; Shaw G.M.; Abdul Razak N. (2023)
Sepsis patients normally suffer microcirculatory dysfunction, which results in organ failure and increased risk of death [1]. Importantly, microcirculatory distress is the only independent factor for predicting patient outcome if it is not treated within 48 hours [2]. Therefore, analyzing oxygen transport and utilization can potentially assess microcirculation function and metabolic condition of an individual. 2012 IEEE.